Exploring Spatial Inequalities in COVID-19 Mortality and Their Association With Multidimensional Poverty in Colombia: A Spatial Analysis Study - Claudia Birchenall-Jiménez; Claudia Birchenall-Jiménez; Wilson Giovanni Jiménez-Barbosa; Javier Riascos-Ochoa; Federico Cosenz (International Journal of Public Health)
ObjectivesThe objective is to examine spatial inequalities in COVID-19 mortality rates in Colombia in relation to the spatial distribution of multidimensional poverty.MethodsA retrospective spatial epidemiological study was conducted in Colombia from 2020 to 2022. Spatial statistics such as Moran’s I index, LISA analysis, and simultaneous autoregressive conditional (SAC) regression models were used.ResultsThe Moran’s I index for different years was as follows: 2020: 0.3 (p = 0.0001), 2021: 0.27 (p = 0.0001), and 2022: 0.26 (p = 0.0001). In 2020, the significant variables were low educational achievement, barriers to early childhood care, child labor, school non-attendance, informal employment, lack of health insurance, inadequate floor material, and critical overcrowding. In 2021, the significant variables were low educational achievement, critical overcrowding, inadequate excreta disposal, and lack of access to water sources. In 2022, the significant variables were school lag and inadequate excreta disposal.ConclusionThis study revealed that in Colombia, a series of socioeconomic and health factors are interconnected and contribute to COVID-19 mortality. These changes may reflect various socioeconomic, political, and environmental dynamics that shifted during the pandemic years.